Rapid metabolism and increased expression of CYP81E8 gene confer high level of resistance to tembotrione in a multiple-resistant Palmer amaranth (Amaranthus palmeri S. Watson) - Aarthy, Thiagarayaselvam; Shyam, Chandrima; Jugulam, Mithila (Frontiers in Agronomy, 2022)
Herbicides, such as tembotrione, that inhibit 4-hydroxyphenylpyruvate dioxygenase (HPPD) enzyme are used to control broad spectrum of weeds, primarily in corn, as this crop can metabolize these herbicides via cytochrome P450 activity. In 2018, a Palmer amaranth (Amaranthus palmeri) population, KCTR was found to be resistant to multiple herbicides including, tembotrione in Kansas (KS), USA. However, the mechanism of tembotrione resistance in KCTR is not known. The objective of this study was to characterize the level of tembotrione resistance and investigate the mechanism of resistance to this herbicide in KCTR using a known susceptible Palmer amaranth population (KSS). Tembotrione dose response experiments revealed that KCTR Palmer amaranth is 23 times more resistant to this herbicide, than KSS. No difference in absorption or translocation of [14C] tembotrione between KSS and KCTR was found. However, the time required to metabolize 50% of tembotrione was shorter in KCTR than in KSS. More than 95% of tembotrione was metabolized at 6 hours after treatment (HAT) in the KCTR, compared to only 50% in KSS plants. Application of cytochrome P450-inhibitors (e.g., malathion or piperonyl butoxide), along with tembotrione reversed the resistance in KCTR. Furthermore, the KCTR plants showed 35-fold increase in constitutive expression of CYP81E8 gene compared to KSS. Nonetheless, the HPPD gene expression was not altered in KCTR Palmer amaranth. Our results suggest that enhanced metabolism of tembotrione possibly due to increased expression of CYP81E8 gene contribute to tembotrione resistance in KCTR. Metabolic resistance to herbicides is a challenge for weed management as such resistance predisposes weeds to evolve resistance to unknown herbicides even without selection.